PENINGKATAN MOTIVASI BELAJAR SISWA MELALUI PENERAPAN MEDIA INTERAKTIF WORDWALL KELAS IV SD - Tika Widiya Ningrum; Savitri Suryandari; Mahyuni Rahayu (TARBIYATUL ILMU: JURNAL KAJIAN PENDIDIKAN, 2025)
The purpose of this study was to increase students' learning motivation in Indonesian language subjects using interactive wordwall media in class IV-D SDN Pakis 1 Surabaya. This research is a Classroom Action Research with the Kurt Lewin model. The subjects in this study were students in class IV-D SDN Pakis 1 Surabaya in the 2024/2025 school year, totaling 28 students.  The method used in this research is the PTK (Classroom Action Research) method. Data collection techniques using questionnaire techniques.  Indicators of success in the study can be measured from the acquisition of learning motivation questionnaire scores that show between 81%-100% which are included in the high category. The results showed that the use of interactive wordwall media can increase students' learning motivation in Indonesian language subjects on narrative text material. This is evidenced by the increase in student learning motivation scores before the action or pre-cycle of 67% in cycle I, increasing from 67% to 82%. Meanwhile, from cycle I to cycle II, there was an increase of 7% to 89% with a high category.